Moral Regulation and the Formation of Ethical Subjects - Velverde, Mariana (Toronto journal of theology, 1996)
Historians have often treated moral reform movements as diversions from the main outlines of history. Dismissing activists in such campaigns as temperance or anti-prostitution as irrational and unworthy of study, or else reducing moral concerns to the socio-economic self-interest of the reformers in question, historians have refused to grapple with moral regulation as an object of serious scholarly study. In the process, important dimensions of the social and cultural history of our society are either dismissed as comical interludes or regarded as mere ruses, covering up "the real story": the control of the working classes and the suppression of their culture (the Marxist version), or the timeless desire of men to control women's behaviour through sexual codes (the feminist version).